Multicomponent exercise program for improvement of functional capacity and lipidic profile of older women with high cholesterol and high triglycerides - Leitão, Luís (2021)
Background: Physical inactivity is a primary cause of most chronic diseases. In addition, the negative effects of aging, physical inactivity and dyslipidemia are risk factors for cardiovascular diseases of older women. Exercise is considered fundamental for the treatment and prevention due to the benefits in the health of this population, but detraining periods after exercise can reverse them. Multicomponent exercise (ME) is a combined method of aerobic and resistance training that can improve the lipidic profile of older women with high cholesterol and triglycerides. Methods: Seventeen older women (EG: 65.3 ± 4.7 years, 1.52 ± 4.12 m) followed a supervised ME program of nine months and three months of detraining (DT), and fifteen older women (CG: 66.4 ± 5.2 years, 1.54 ± 5.58 cm) continued their daily routine, without exercise. Total cholesterol (TC), triglycerides (TG), blood glucose (GL) and functional capacity (FC) were evaluated at the beginning and at the end of the program and after three months of DT. Results: ME program improved (p < 0.05) lipidic profile: GL (−15.6%), TC (−15.3%), TG (−19.3%) and FC: agility (−13.3%), lower body strength (27.78%), upper body strength (26.3%), cardiorespiratory capacity (11.2%), lower body flexibility (66.67%) and upper body flexibility (85.72%). DT declined the lipidic profile and FC (p < 0.05). Conclusion: Lipidic profile and functional capacity can be improved with nine months of ME. Besides the negative effects of DT, three months were not enough to reverse the benefits of exercise in older women with high values of TG and TC.